Risk factors of stunting in children aged 24-59 months - Arya Krisna Manggala; Komang Wiswa Mitra Kenwa; Made Me Lina Kenwa; Anak Agung Gede Dwinaldo Putra Jaya Sakti; Anak Agung Sagung Sawitri (Indonesian Pediatric Society, 2018)
Abstract Background Childhood stunting (low height-for-age) still remains a global health problem because it increases the risk of disturbances in growth and development as well as mortality. The prevalence of stunting in Bali is 32.5%, with the highest in Gianyar District at 41%. However, little is known about the risk factors of stunting children in Gianyar. Objective To investigate the risk factors of stunting in children aged 24-59 months in Gianyar. Methods This cross-sectional study involved 166 children, collected consecutively, aged 24-59 months, who visited the integrated health posts in 13 community health centers in Gianyar District, Bali from September to November 2016. Stunting is defined as -2SD below the WHO height-for-age z-score (HAZ), according to sex. Statistical analyses were done with Chi-square and multivariate logistic regression tests. Results Of 166 subjects, 37 (22.3%) children were stunted. Multivariate analysis revealed that low paternal education (AOR 2.88; 95%CI 1.10 to 7.55; P=0.031), maternal height less than 150 cm (AOR 7.64; 95%CI 2.03 to 28.74; P=0.003), high risk maternal age (AOR 4.24; 95%CI 1.56 to 11.49; P= 0.005), low birth weight (AOR 5.09; 95%CI 1.03 to 25.31; P=0.047), and low birth length (AOR 9.92; 95%CI 1.84 to 53.51; P=0.008) were strongly associated with stunting. Conclusion Risk factors for stunting in children are low paternal education, maternal height less than 150 cm, high risk maternal age, low birth weight, and low birth length.